Peran Infrastruktur, Modal Manusia, dan Keterbukaan Perdagangan Ekonomi Terhadap Pertumbuhan Ekonomi - Wulandari, Lili; Estrellita, Mellba; Lamongga, Rizki Ferdiansa; Panorama, Maya (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2023)
Economic growth is the basis of a country's progress. Economists identify various challenges and issues surrounding economic growth. Some common issues include international trade, infrastructure, education, and workforce skills. The aim of the research is to determine the role of development factors on economic growth. These development factors include infrastructure, human capital, and openness to economic trade which will influence economic growth. The method used in researching this article is through literature study. Literature study is to obtain information through notes, literature, documentation and other things that are still relevant to this research. The role of infrastructure, human capital, and economic growth have a significant role in economic growth. Infrastructure development has a role in encouraging economic growth, both at the national and regional levels, as well as in reducing unemployment levels, alleviating poverty, and of course, improving community welfare. In the context of human capital, the Indonesian government continues to invest through various programs to improve the quality of the role of human capital in economic growth. As well as policy planning to utilize the benefits of the role of trade openness while still protecting vulnerable sectors, in attracting foreign capital investment.